1980
DOI: 10.1093/clinchem/26.3.496
|View full text |Cite
|
Sign up to set email alerts
|

Binding of IgG and other proteins to microfilters.

Abstract: We evaluated 10 microfilters for their ability to filter diluted sera without removing immunoglobulins (Ig) G, A, and M, albumin, and transferrin. In general, filters containing cellulose nitrate remove IgG from solution, the amount adsorbed being proportional to the IgG concentration in the solution. With some sera we noted IgA and IgM adsorption to cellulose-nitrate-containing filters, but there was no significant adsorption of albumin or transferrin to any of the filters. We also found that cellulose-nitrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…I t is suggested that a saturation of binding sites of these hydrophilic filters might be the reason why adsorption stops. T h e same phenomenon is observed by Walsh & Coles in studying binding of immunoglobulins to microfilters (19). T h e loss of the investigated drugs by filtration is only temporary and returns to a 100°, recovery value.…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 80%
“…I t is suggested that a saturation of binding sites of these hydrophilic filters might be the reason why adsorption stops. T h e same phenomenon is observed by Walsh & Coles in studying binding of immunoglobulins to microfilters (19). T h e loss of the investigated drugs by filtration is only temporary and returns to a 100°, recovery value.…”
Section: R E S U L T S a N D Discussionsupporting
confidence: 80%
“…Similar binding between neutral molecules, for instance proteinaceous and cellulose filters, was described in an earlier work, which lists the following hierarchy of adsorption to filter materials: cellulose nitrate > mixed cellulose esters > cellulose diacetate > cellulose triacetate. The study with IgG (immunoglobulin) G, A, and M; albumin; transferrin; and other proteins’ adsorption confirms the fact that cellulose nitrate adsorbs the most strongly. One explanation is that IgG has a configuration that allows binding to the chemical structure of the filter material.…”
Section: Results and Discussionsupporting
confidence: 55%
“…Walsh et al 48 observed that cellulose-nitrate-containing filters remove IgG and to a lesser extent IgA and IgM, but there was no significant adsorption of albumin or transferrin by any of the filters studied. If the filters were pre-washed with polyethylene glycol, IgG adsorption was not seen.…”
Section: Absorption Of Proteinsmentioning
confidence: 89%